(untitled) (Proceedings OPTIMAL, 2025)
Background : Nurses are expected to adhere to the nursing code of ethics in their interactions with both fellow professionals and patients. In their daily practice, nurses frequently encounter ethical dilemmas involving both patients and coworkers. Nursing ethics are essential for fostering respectful and effective relationships with patients and colleagues alike. Despite this, a significant number of nurses continue to angage in practices that do not align with the established code of ethics. Objectives : This research seeks to explore the overview of nurses’ ethical behavior toward colleagues and their ethical attitudes toward patients. Methods : This research employs a quantitative, non-experimental approach with a descriptive design to explore the subject matter. The research was carried out between March and August 2023. The sampling technique used in this study was purposive sampling. A total of 101 participants were selected based on predetermined inclusion established by the researcher. Results : The majority of nurses at Sleman Regional Public Hospital displayed very good ethical behavior toward their colleagues, with 74 nurses (72,5%) falling into this category. Most nurses at Sleman Regional Public Hospital demonstrated a moderate level of ethical attitude toward patients, accounting for 52 nurses (51%). The study further identified significant associations between nurses’ age and length of service with both their ethical behavior toward colleagues and their ethical attitudes toward patients. Conclusion : None of the nurses at Sleman Regional Public Hospital demonstrated moderate or poor ethical behavior toward peers, nor were there any reports of poor ethical attitudes toward patients.